TEORI MULTIPLE INTELLIGENCES DAN IMPLIKASINYA TERHADAP PENGELOLAAN PEMBELAJARAN - Amir Hamzah (State Islamic Institute of Madura, 2009)
The article clarifies Howard Gardnerâ€™s Multiple Intelligence theory. He states that the theory serves nine kinds of intelligences—linguistic, logical-mathematical, spatial, bodilykinestheticc, musical, interpersonal, intrapersonal, naturalistic, and existential. The theory claims that infants have different intelligences, moreover it influences learning orientation. It enables students to comprehend the subjects more easily, if the subjects are presented based on the studentsâ€™ potencies. Yet, it is important for the teachers to understand the theory to accelerate the learning process and output.